Analysis of means for monitoring air pollution in the environment - Запорожець, А. О. (Science-based technologies, 2017)
The features of air pollution monitoring in the environment are considered in the article. Harmful substances that formed during the combustion of various types of fuels on heat generating objects are analyzed. Approaches to simulation of emission distribution by thermal power facilities in the surface layer are investigated. Features of the functioning of automated air pollution control systems in different countries of the world are considered. The approach to monitoring ambient air pollution based on unmanned aerial systems was proposed, and its advantages are showed.